SELF-CONFIDENCE OF NURSES TO TREAT SUDDEN DETERIORATION PATIENTS IN MEDICAL WARDS - AHMAD IKHLASUL AMAL (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2016)
Background: Sudden deterioration defined as a condition in which a progression over a complex illness. Progression of pain to the patient causing displacement status characterized by the vital signs of patients who experienced abnormality. Nurses in medical and surgical ward almost everytime facing with patients with acute deterioration conditions. Nurses should have confidence when giving proper treatmen for acute patents deterioration. Methods: This study utilize quantitative descriptive research conducted in the hospital ward illness Islam Sultan Agung Semarang. The number of respondents that used in this study were 98 nurses, utilized consecutive sampling technique. Results: The results showed that the average level of confidence gained nurses treating patients in the ward conditions of acute deterioration in the disease is expressed 3.03. It is mean that respondents have moderate level of confidence. Conclusions: The level of confidence of nurses in treating patients with acute exacerbation of conditions needs to be improved to provide excellent service qualityKeywords: nurse, self-confidence, sudden deterioration